Marijuana use and short-term outcomes in patients hospitalized for acute myocardial infarction - Johnson-Sasso, Cecelia P. (PLoS One, 2018)
Marijuana use is increasing worldwide, and it is ever more likely that patients presenting with acute myocardial infarctions (AMI) will be marijuana users. However, little is known about the impact of marijuana use on short-term outcomes following AMI. Accordingly, we compared in-hospital outcomes of AMI patients with reported marijuana use to those with no reported marijuana use. We hypothesized that marijuana use would be associated with increased risk of adverse outcomes in AMI patients. Hospital records from 8 states between 1994–2013 were screened for patients with a diagnosis of AMI. Clinical profiles and outcomes in patients with reported use of marijuana were compared to patients without reported marijuana use. Short-term outcomes were defined as adverse events that occurred during hospitalization for an admitting diagnosis of AMI. The composite primary outcome included death, intraaortic balloon pump placement, (IABP), mechanical ventilation, cardiac arrest, and shock. In total, 3,854 of 1,273,897 AMI patients reported use of marijuana. The marijuana cohort was younger than (47.2 vs. 57.2, respectively) and had less coronary artery disease than the non-marijuana cohort. In multivariable analysis including age, race and common cardiac risk factors, there was no association between marijuana use and the primary outcome (p = 0.53), but marijuana users were more likely to be placed on mechanical ventilation (OR (odds ratio) 1.19, p = 0.004). Interestingly, marijuana-using patients were significantly less likely to die (OR 0.79, p = 0.016), experience shock (OR 0.74, p = 0.001), or require an IABP (OR 0.80, p = 0.03) post AMI than patients with no reported marijuana use. These results suggest that, contrary to our hypothesis, marijuana use was not associated with increased risk of adverse short-term outcomes following AMI. Furthermore, marijuana use was associated with decreased in-hospital mortality post-AMI.